Ethics for Adversaries : The Morality of Roles in Public and Professional Life - Applbaum, Arthur Isak (Book collections on Project MUSE., 2001)
The adversary professions--law, business, and government, among others--typically claim a moral permission to violate persons in ways that, if not for the professional role, would be morally wrong. Lawyers advance bad ends and deceive, business managers exploit and despoil, public officials enforce unjust laws, and doctors keep confidences that, if disclosed, would prevent harm. Ethics for Adversaries is a philosophical inquiry into arguments that are offered to defend seemingly wrongful actions performed by those who occupy what Montaigne called "necessary offices."Applbaum begins by examinin.